Application of Low Cost Novel Bio Sorbent, Textured Vegetable Protein- In Treatment of Industrial Wastewater (International Journal of Innovative Research in Computer Science & Technology, 2022)
Toxic metals are produced and dumped  into water supplies by various anthropogenic activities, for  example, industrial effluents, making them inaccessible  and threatening human health. Conventional chemical  precipitation and membrane filtration are two methods for  elimination of toxic elements and are exceedingly costly  when treating large amounts of water, and ineffective at  low metal concentrations (incomplete elimination) can  produce large amounts of sludge and other harmful  compounds, which necessitate disposal with care.  Biosorption is environmentally acceptable option that offer  advantages over other methods. Natural and other agro based materials that are abundant, such as microbial agro wastes, biomass, and industrial leftovers, have been  proposed as suitable biosorbents for heavy metal removal.  Temperature, pH, metal ion concentration, biosorbent  dose, and agitation speed are all factors that influence  biosorption. Before usage, the biomass might be  chemically and physically altered. By renewing and  recycling the biosorbent after it has removed heavy metals  from wastewater, the process can be made more cost effective. Various bioreactors could be used to eliminate  toxic metal ions from large volumes of effluents or water  in biosorption. In biosorption, a variety of bioreactors can  be used to remove metal ions from huge volumes of  effluents or water. The current study looks at the future  potential of textured vegetable protein (TVP) or Soya  Chunks in the biosorption of industrial effluent, with a  prime focus on Chromium and Lead.
Keywords: Agro waste; biosorption; heavy metal; Textured Vegetable Protein; biosorbent